1984
DOI: 10.1177/009579848401100104
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Change in Self-Perception and Achievement Among Black Adolescents: A Longitudinal Study

Abstract: This study of self-perception and achievement among Black adolescents surveyed 248 thirteen- and fourteen-year-old eighth graders in 1980 who were previously surveyed as ten- and eleven-year-old fifth graders in 1977. The major devel opmental dimensions investigated were stability—whether or not these youngsters exhibited self-perception and/or achievement patterns of an erratic turmoil ridden or con tinuous nature, and chunge—the nature of the differences found in self-perception and achievement between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Given the possible importance of academic self-beliefs in promoting academic achievement and preventing drop-out, the results are rather alarming. Previous research on urban adolescents in metropolitan areas (Hare, 1985;Lay & Wakstein, 1985) has suggested the relatively smaller role of academic self-perceptions in determining the overall self-esteem of African-American adolescents. This has been considered to be one of the major differences between African-American and White adolescents.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Given the possible importance of academic self-beliefs in promoting academic achievement and preventing drop-out, the results are rather alarming. Previous research on urban adolescents in metropolitan areas (Hare, 1985;Lay & Wakstein, 1985) has suggested the relatively smaller role of academic self-perceptions in determining the overall self-esteem of African-American adolescents. This has been considered to be one of the major differences between African-American and White adolescents.…”
Section: Discussionmentioning
confidence: 96%
“…Although the relationship between academic achievement and self-concept has been found to be positive and significant among White adolescents (Mboya, 1988), it does not seem to hold among African Amencans. Although African-American adolescents have consistently scored higher than Whites on measures of general self-esteem, as well as self-beliefs regarding attributions of attractiveness and popularity, their self-beliefs in school-related areas have been lower than Whites' (Hare, 1985). Hare (1985) suggested that the African-American adolescent might base his or her self-perceptions on different types of self-related information than the White adolescent does.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However, work in this area is growing quickly, with much of it focusing on the academic problems and prospects of African American (see Hare, 1985;Meece & Kurtz-Costes, 2001;Slaughter-Defoe, Nakagawa, Takanishi, & Johnson, 1990), Mexican American (e.g., Padilla & Gonzalez, 2001;Portes & Rumbaut, 2001), and Asian American youth (Fuligni & Tseng, 1999; S. J. Lee, 1994), both those born in this country and those who have immigrated here.…”
Section: The Development Of Group Differences In Motivation: the Rolementioning
confidence: 99%